Income differences among elderly in Malaysia : a regional comparison. - Masud, Jariah; Haron, Sharifah Azizah (Wiley-Blackwell, 2008)
Malaysian economic development, formally launched in 1970 through a series of 5-year development plans, has tremendously improved the quality of life of its citizens. Unfortunately, varying degrees of regional development that lead to regional imbalances produce differential impact on different sets of population in each region. This is especially true for the poverty-prone groups, which include the elderly, women and children. This study attempts to assess regional differences (between West and East Malaysia) in the well-being of the elderly as indicated by the income inequality. Specifically, the objectives of this study are to identify sources of elderly income, to determine the mean monthly income and to examine elderly income disparity in the three regions of Peninsular, Sabah, and Sarawak in Malaysia. A total of 2327 elderly respondents were randomly selected nationwide using the stratified random sampling technique. The study indicated that generally, the income of the elderly in Malaysia is very low as most of them had received no formal education or had only obtained primary school education. In terms of income disparity, the elderly income distribution in Sabah showed an interesting pattern, whereby a high percentage of the elderly was clustered in the bottom 20 and top 20 percentile. However, the distribution of the elderly in Peninsular Malaysia was clustered around the bottom 40 percentile, the middle 60 and the top 40 percentile.